Small Bowel Melanoma Metastasing to Inguinal Lymph Node - a Rare Case - Chisthi M., Meer (Indian J Surg Oncol, 2015)
Malignant Melanoma is one of the commonest cutaneous malignancies affecting human beings. The gastrointestinal tract is a common site for melanoma, both as primary and metastases. However it is rare for gastrointestinal melanoma to metastase oustide of the abdominal cavity. In the literature, there is no evidence about inguinal lymph node metastases from small bowel melanoma. Here we present a case report of an old lady who underwent laparoscopic resection of small bowel for melanoma and presented 4 years later with metastatic lymph node in inguinal lymph node. Though it could not be verified, we hypothesise that the tumour disseminated to the lymph node through a port-site metastases. Literature review shows several mechanisms which were put forward to explain the mechanism of port-site metastases.